Farmers’ preference for bundled input–output markets and implications for adapted dairy hubs in Tanzania—A choice experiment - Rao, E.J.O.; Mtimet, Nadhem; Twine, Edgar E.; Baltenweck, Isabelle; Omore, Amos O. (Wiley, 2019)
Dairy business hubs (DBHs) are flexible mechanisms for linking farmers to input and output markets. Yet participation by smallholders in these hubs will only be realized if the hub options are adapted to the needs of farmers. We analyze preference for DBHs in Tanzania using survey data from smallholder dairy producers in Tanga and Morogoro. Applying choice experiment method, we find significant preference for hub options with higher milk prices and payment for milk on a fortnight rather than cash basis. Farmers also prefer options that bundle milk marketing with input provision. For bundled inputs, farmers prefer hub options that allow payment for such inputs via credit or check‐off rather than cash. Our analyses also reveal significant heterogeneity in preference among farmers that should be considered in adapting dairy hubs to Tanzania. Emerging dairy hubs in Tanzania should be supported to either establish in‐house input provision arrangements or to enter contracts with agro‐input dealers in their environs. [EconLit citations: C25, C99, Q13]